The determinants and relationship of customer perceived factors on loyalty for electrical and electronic product brands in Sarawak / Gloria Panit - Panit, Gloria (2013)
Customer loyalty is about appealing to the right customer, getting them to buy often and in higher quantities, as well as bringing in more customers. Although, many studies on loyalty have been done (e.g. Huang, 2009; Rowley, 2005; Reichheld, 2000), studies on factors affecting customer loyalty needs further attention especially for electrical and electronic product brands in developing countries. Furthermore, studies on loyalty have found dissimilar findings. 1971 respondents were selected for the purpose of this study. They are customers of EEP brands generally the households. These respondents were selected from four major cities of Sarawak. This study identified that there are eight important factors which affect customer loyalty on EEP brands. Using factor analysis, the components are grouped into the respective factors; country of origin (COO), brand equity (BE), satisfaction (SAT), affect, resistance to change (RTC), value, trust and corporate reputation (CR). Using multiple regression analysis, the results indicated that there are six variables affecting customer loyalty. The factors are RTC, CR, affect, SAT, values and BE, significantly the strong factors predicting customer loyalty on EEP brand. COO and trust factors are found not to be strong predictors. The findings suggested that Malaysian have low ethnocentric tendencies and do not stress on cultural differences. In addition, customers ranked the factors according to their importance. It was found that the order of the most important factors contributing to customers' loyalty is SAT followed by CR, COO, BE, trust, RTC, value and affect factors respectively. Comparisons between foreign and local EEP brands were also made. This study found that customer loyalty is influenced by the COO factor towards buying foreign brands; otherwise the concern is more on SAT factor when buying local brands. However, CR is the least important factor influencing customer loyalty to both local and foreign EEP brands. Further, it was found that there is a significant positive relationship between customer perceived factors and loyalty. The findings pointed out that as the importance of customer perceived factors increase, the higher level of loyalty would be.